Sakralitas Pernikahan dalam Cahaya Al-Qur'an : Sakralitas Pernikahan dalam Cahaya Al-Qur'an - Syaripah Aini (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2024)
Marriage is one of the social institutions that has an important position in Islam, not only as a means of fulfilling biological needs, but also as a form of worship that has high spiritual value. This article aims to examine the concept of the sacredness of marriage from the perspective of the Qur'an, by highlighting the values ??of faith, harmony, and responsibility that are the foundation of an Islamic household. A thematic interpretation approach is used to explore the meaning of relevant verses of the Qur'an, such as Surah Ar-Rum verse 21 on mawaddah wa rahmah (love and affection) and Surah An-Nisa verse 34 on the roles and responsibilities of husband and wife. The results of the study show that marriage in Islam has a deep spiritual dimension, namely as a mitsaqan ghalizha (a heavy covenant) that connects a husband and wife with Allah swt. In addition, the sacredness of marriage is also reflected in the guidance of the Qur'an which emphasizes the importance of good communication, mutual understanding, and commitment to building a family that is sakinah (peaceful), mawaddah (full of love), and rahmah (affectionate). Thus, a deep understanding of the sacredness of marriage in the Al-Qur'an can be a guide for Muslims in building a harmonious domestic life and the approval of Allah swt.